MEREBUT PEMERINTAH UNTUK KEDAULATAN RAKYAT - Sutoro Eko (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2021)
In contrast to the idea of "reclaiming the state", this paper presents the idea of "reclaiming the government" for the sovereignty of the people. There are two reasons that hit it. First, the scarcity of "government theory" in governmental science and study. Various theories and studies (sociology, economics, politics, law, administration, management) place government as an object, without forming the whole theory of government. Second, the practices of governance without government. Although Indonesia formally has a government, it is not a government in the true sense of the principles of republicanism and constitutionalism. So to uphold the people's sovereignty, it is important to reclaim the government from bureaucracy, technocracy, development, and markets. This can be done with thought dan struggle. Governmental science can contribute by making endogenous government theories (institutions, political-economy, and governmentality) and use that theory to study government, human phenomena, and people's interests.